Laser-Degeneration Study of Nerve Fibers in the Optic Nerve - Carri, Néstor (1980)
Knowledge about wiring of neurons is one of the most important goals of neurobiology. Neuronal processes -axons and dendrites- degenerate when they are severed from their cell body. Since different staining procedures distinguish between the degenerating axons and their healthy neighbors, most neuroanatomical pathways have been mapped through the follow-up of degenerating axons after spontaneous or experimental lesions at some point of the pathway. Mapping of neuroanatomical connections has been enormously enriched during the past few years, thanks to new labelling techniques with great resolution power [1]. However, the resolution of the older degeneration procedures is only limited by the extent of the lesion and the resolution of the differential staining of degenerating axons. As we will show in this report, the use of a laser to produce small lesions in the retina of birds, coupled to the detection of degenerating axons in semi-thin plastic sections [2] is allowing us to understand the relationship between axons along the optic pathway with a resolution comparable to that of “in vivo” labelling techniques.